KUALITAS ILUSTRASI BUKU TEKS TEMATIK TERPADU TEMA â€œKELUARGAKUâ€ JILID 1D TERBITAN ERLANGGA - Lusiatania Ayu; Noor Riyadhi (Jurnal Ilmiah Publipreneur, 2014)
This research aims to examine the quality of the illustration image in an integrated thematic textbooks for the theme of "Keluargaku" Vol 1D published by Erlangga. The researcher uses a qualitative descriptive method, with literary research, observation and interview. In the end, it can be concluded that there are errors of as much as 30% illustration images and the use of the illustration is not fully in accordance with the concept of thematic for Curriculum 2013. First, the layout of illustrations in this book are already onsite according to the style that is applied by the publisher. Second, the depiction of the characters in this book not quite maximum. Third, representations of techniques in this book are computerized process thoroughly. Fourth, the quality of the illustrations in this book concerns three aspects, namely: mouth-watering readers, the quality of the message, as well as clarity and precision.